Photon-Assisted Seebeck Effect in a Quantum Dot Coupled to Majorana Zero Modes - He, Tian-Yu; Sun, Hailing; Zhou, Guofu (Frontiers in Physics, 2021)
Seebeck effect in a quantum dot (QD) sandwiched between the left and right leads held at different temperatures is investigated within the framework of nonequilibrium Green’s function technique. We consider that the QD is shelled by a photon field and is side-coupled to a topological superconductor nanowire hosting Majorana zero modes (MZMs). It is found that the thermopower (Seebeck coefficient) can be obviously enhanced by weak QD-MZMs coupling at low temperatures, in addition to its sign reversion that may be used for detecting the existence of MZMs. In the presence of a photon field, the thermopower can be further enhanced due to decreased electrical conductance when electrons’ transport probability through each channel is reduced by photon-assisted tunneling (PAT). The hybridization between the MZMs will also induce sign reversion of the thermopower in the absence of a photon field, whereas it has less impact on the thermopower when the QD is shelled by the photon field.